INOVASI LAYANAN PENELUSURAN INFORMASI JURNAL ELEKTRONIK PADA WEB PERPUSTAKAAN DALAM MENDUKUNG KEGIATAN PENELITIAN DAN PENGEMBANGAN DI PUSLITBANG JALAN DAN JEMBATAN, BADAN PENELITIAN DAN PENGEMBANGAN, KEMENTERIAN PUPR - Anita Rahmawati (Jurnal IPI (Ikatan Pustakawan Indonesia), 2019)
Information Retrieval Services is the primary key from the library because people who need information can find what they need through nformation retrieval.. This article describes the new innovation of information retrieval services at Pusjatan’s library. The method of this articles is literature review and case study in Pusjatan’s Library. The result is, electronic journal (e-journal) is one of e-resources in Pusjatan’s library which can support the research in Pusjatan. The information retrieval can be done by using electronic tools to access e-journal as e-resources based on web Pusjatan’s library.